Effect of biochar and chicken manure on growth performance and phytochemicals of Orthosiphon stamineus (Misai kucing) - Khusaini, Mohamad Faeez (2015)
The effective of biochar and chicken manure on the growth performance and phytochemicals of misai kucing (Orthosiphon stamineus) were studied. Misai kucing was planted in a glasshouse at Ladang 2, Universiti Putra Malaysia. In this experiment, there were 9 treatments combinations and 4 replications, from three biochar rates (0, 5 and 10 ton/ha) and three chicken manure rates (0, 2.5 and 5 ton/ha) are arranged in a randomized complete block design. The plants were harvested 10 weeks after transplanting. The parameters measured were plant height, days to flowering, chlorophyll content, fresh and dry weights and phytochemical contents (total phenolic and total flavonoid contents and antioxidant activity). The phytochemical contents were extracted from whole plant by using methanol extraction of dry sample O. Stamineus. The Folin-Ciocalteu method was used for phenolic contents determination, aluminum chloride colorimetric method for determination of flavonoid contents and 2,2-diphenylpicrylhydrazyl method for determination of antioxidant activity. Biochar had no significant effect on plant height, days to flowering and fresh weight among the rates of biochar application. Chicken manure significantly affected plant height, days to flowering, chlorophyll content, fresh weight and dry weight. The biochar affected the phenolic contents, but was not significantly affected by the chicken manure rates applied. Total flavonoid contents did not show significance in the presence of biochar and chicken manure. The antioxidant activity was significantly affected by the rates of biochar and chicken manure used as soil amendments. However, it is recommended that further research should be done to investigate the long-term effects of the combination of biochar and chicken manure as a soil amendment on the growth performance and quality of O. stamineus.